Unexpected One-Pot Synthesis of 3-Cinnamoyl-3-hydroxyphthalide Derivatives - Rakchaya, Intouch; Thongaram, Phanida; Saiyalard, Sengchan; Yimnoi, Kredmanee; Wattanathana, Worawat; Chuanopparat, Nutthawat; Ngernmeesri, Paiboon (Synlett, 2024)
A new and simple method to prepare 3-cinnamoyl-3-hydroxyphthalide derivatives from 2-hydroxy-3-methyl-1,4-naphthoquinone and substituted benzaldehydes was unexpectedly uncovered. The reaction was conveniently performed in DMSO at 100 °C with K3PO4 as a base and AlCl3 as a catalyst. We propose that the reaction proceeds by a cascade process involving nucleophilic addition followed by demethylation and rearrangement. The products were typically obtained in moderate to good yields. The highest yield (95%) was obtained when the reaction of 2-bromobenzaldehyde was performed for 24 hours. X-ray crystallography of the product derived from 2-fluorobenzaldehyde unequivocally confirmed the structure of the hydroxyphthalide derivatives.
Keywords: hydroxyphthalides; one-pot synthesis; cascade reaction; natural product; benzaldehydes